2010
DOI: 10.1159/000320858
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Peritoneal Washing Cytopathology in Ovarian Carcinomas and Tumors of Low Malignant Potential: A Quality Control Study with Literature Review

Abstract: Objective: The author evaluated a consecutive group of peritoneal washings (PWs) performed in the evaluation of adnexal masses to determine whether the conventional histopathologic prognostic parameters significantly affect the tumor detection rate using this procedure. Study Design: Cytopathologic reports from all PWs performed over a 13-year (1996–2008) period in the evaluation of malignant and borderline ovarian tumors were reviewed and correlated with those of the synchronously obtained histopathologic spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Our case presented as stage III-B disease. Positive peritoneal cytology rates increase with advancing tumor stage (7). In our case, cytology was also positive.…”
Section: Discussionsupporting
confidence: 64%
“…Our case presented as stage III-B disease. Positive peritoneal cytology rates increase with advancing tumor stage (7). In our case, cytology was also positive.…”
Section: Discussionsupporting
confidence: 64%
“…Fifteen (33 %) of high-grade tumors showed negative histology. Ozkara reported that PW were significantly more likely to yield malignant cells in higher grade than lower grade tumors [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exfoliation of tumor cells in peritoneal washing samples raises the FIGO stage from IA/IB or IIA/IIB to stage IC or IIC despite the absence of a grossly visible tumor. [1] However, stage is the most important prognostic factor for AGCT. [5] Sun et al .…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, while it is important for tumor staging, it is very difficult to identify the presence of rare tumor cells and to diagnose AGCT using peritoneal washing. Cytological examination of tumor cells has mostly focused on samples obtained using fine-needle aspiration and ascitic fluids.…”
Section: Introductionmentioning
confidence: 99%